Estimativa do número de crianças e adolescentes em situação de rua em dois municípios do Brasil através do método captura-recaptura - Bezerra, Kátia Floripes (2007)
Aims: To estimate the number of street children and adolescents in Maceió and Arapiraca, northeast Brazil, describe the characteristics of this population. Methods: The number of children and adolescents in street situation in Maceió and Arapiraca was estimated using the Capture-Recapture method and calculated with log-linear method. Three independent lists of children and adolescents in street situation of each municipality were constructed. In each municipality in was obtained on official list and two other lists from surveys. Each survey took the entire day, the first in a week day (Wednesday) and the other in the following Saturday. The characteristics of the children were recorded during the street surveys. Results: The estimated number of children and adolescents in street situation was 4965 in Maceió and 466 in Arapiraca. The population estimated before was 565 in Maceió and 158 in Arapiraca. In Maceió most street children and adolescents were male (71,4%) and (71,80%), who maintain contact with their families (85,3%) and (89,60%) and frequent the school (43,4% and (49,70%), drug use was referred for 47,00% of the children and adolescents in Maceió and (26,6%) in Arapiraca glue associated on not with other drug was the most cited one. Conclusion: children and adolescents in street situation is a common event in Maceió and Arapiraca and individuals envolved have similiar characteristics to street children from other countries and other cities in Brazil. The estimated number of street children and adolescents, calculated by Capture-Recapture method is coherent to the cities socioeconomic and demographic status. The method of Capture-Recapture seems to be suited to study mobile populations such as street children and adolescent good reproducibility.